PALYNOSTRATIGRAPHIC STUDIES OF CRETACEOUS DEPOSITS OF ANAMBRA BASIN, EASTERN NIGERIA (Biological Sciences - PJSIR, 2004)
Upper cretaceous strata of Anambra basin were spot sampled at two locations. A palynological investigation of the forty-one samples from the outcrop section, enabled the recognition of five palynological zones based on pollen and spores. The assemblage zones which are assigned upper Campanian to Maestrichtian age are: a). Tricolpites/Syncolporites/ Matonisporites Assemblage zone (upper Campanian). b). Psilamonocolpites/Zlivisporis Assemblage zone (Campanian- Maestrichtian). c). Retistephanocolpollenites/Monocolpollenites/Propylipollis Assemblage zone (Maestrichtian). d). Retidiporites/Verrucatosporites/Buttinia Assemblage zone (Maestrichtian) and e). Rugulatisporites/Cingulatisporites Assemblage zone (Maestrichtian). The dominance of the palynomorph assemblage by trilete spores (Cingulatisporites ornatus, Foveotriletes margaritae, Zlivisporis blanensis, and Verrucatotriletes bullatus) and monocolpites (Monocolpites marginatus, Longapertites sp. and Monocolpollenites sp.) indicate a swampy environment fringed by herbaceous vegetation. While the dark grey to black, fissile, sulphur stained, pyretic, lignitic and laminated carbonaceous shale suggested a tidal flat environment of deposition. This study therefore enabled the recognition of five informal palyno- logical zones in the upper Cretaceous sediments of Anambra basin and tidal flat environment.